How the COVID-19 pandemic is focusing attention on loneliness and social isolation - Ben J Smith; Michelle H Lim (Public Health Research & Practice, 2020)
The effects of the coronavirus disease 2019 (COVID-19) pandemic upon human health, economic activity and social engagement have been swift and far reaching. Emerging evidence shows that the pandemic has had dramatic mental health impacts, bringing about increased anxiety and greater social isolation due to the physical distancing policies introduced to control the disease. In this context, it is possible to more deeply appreciate the health consequences of loneliness and social isolation, which researchers have argued are enduring experiences for many people and under-recognised contributors to public health. In this paper, we examine the social and psychological consequences of the COVID-19 pandemic, with a focus on what this has revealed about the need to better understand and respond to social isolation and loneliness as public health priorities.